Building High-tech Agricultural Cooperative Model Aimed at Expanding the Purple Sugarcane Consumption Market in Tan Lac District, Hoa Binh Province - Thi Tu Anh, Dang; Phuong Trang, Nguyen; Hong Van, Dinh; Thi Van, Dinh; Thi Ngoc Anh, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 40 No 2, 2024)
Purple sugar cane is one of the key agricultural products of Hoa Binh Province with a relatively large production area. In recent years, purple sugarcane in the province has not only been consumed domestically but also expanded for export. However, finding a stable output market for this agricultural product in Tan Lac district, Hoa Binh province still faces many difficulties. Even though there are production and consumption parameters of a cooperative unit, the scale of the contract is still limited and does not ensure a stable output market. Recognizing that Tan Lac district has suitable conditions to apply the high-tech agricultural cooperation model for purple sugarcane, the article focuses on assessing the current state of production as well as pointing out difficulties and barriers in developing the market for purple sugarcane. From there, combined with lessons learned, the authors proposed the application of a high-tech cooperation model in Tan Lac district, Hoa Binh province. The application of this model will help the locality expand consumption market opportunities for purple sugarcane agricultural products.